Production of cyanobacterial toxins from two Nostoc species (Nostocales) and evaluation of their cytotoxicity in vitro - RUMEN MLADENOV; IVANKA DIMITROVA-DYULGEROVA; DETELINA BELKINOVA; PLAMEN STOYANOV; IVANKA TENEVA; BALIK DZHAMBAZOV (Journal of BioScience and Biotechnology, 2012)
Cyanobacteria are among the oldest autotrophic organisms with cosmopolitan distribution and known as producers of secondary metabolites with toxic properties named "cyanotoxins". Studies with respect to toxin production of genus Nostoc are yet limited. In the present study we have investigated two Nostoc species (Nostoc linckia and Nostoc punctiforme) for production of intracellular and/or extracellular compounds with cytotoxic potential. Extracts and algal growth media were assessed by different in vitro tests using freshly established mouse primary cultures from different tissues and one fish cell line. Our data showed that the mouse cells are more sensitive to toxic compounds than the fish cells. Both Nostoc species produced intracellular and extracellular bioactive compounds with different effects on mouse and fish cells. The presence of cyanotoxins as anatoxin-a and microcystins/nodularin was confirmed by HPLC and ELISA analyses. Therefore, Nostoc species are not only sources of bioactive compounds with therapeutic action, but they can be a potential hazard to aquatic systems as well as to animal and human health.